Caracterización Fitoquímica, Compuestos Fenólicos, Actividad Antioxidante y Contenido de Micronutrientes en Extracto de Hojas de Psidium guajava L. - Loyola-Gonzales, Eddie (2025)
Background: Psidium guajava L. is a species widely used in traditional medicine, mainly due to its diversity of secondary metabolites with reported antioxidant properties and nutritional benefits. However, the marked variability in its phytochemical and mineral composition highlights the need for scientific evidence to rigorously support its nutraceutical potential. Materials and Methods: Fresh leaves of P. guajava were collected, dehydrated, pulverized, and subjected to ethanol maceration. The phytochemical profile was characterized through standardized qualitative assays. Total phenolic and flavonoid contents were quantified using the Folin–Ciocalteu and aluminum chloride methods, respectively. Antioxidant activity was assessed through DPPH and ABTS assays. In addition, micronutrient concentrations (Ca, Mg, Fe, Zn, and Cu) were analyzed by atomic absorption spectroscopy. Data were statistically processed using ANOVA followed by Tukey’s test (p < 0.05). Results: The ethanolic extract revealed the presence of flavonoids, tannins, saponins, terpenoids, and alkaloids. The concentration of phenolic compounds reached 96.4 ± 2.3 mg GAE/g, while flavonoids accounted for 41.7 ± 1.6 mg QE/g. Antioxidant capacity showed an IC50 of 34.2 ± 1.1 µg/mL in the DPPH assay and 612.5 ± 15.3 µmol TE/g in ABTS. Regarding mineral composition, calcium (142.7 ± 3.9 mg/100 g), magnesium (88.3 ± 2.6 mg/100 g), and iron (21.4 ± 1.1 mg/100 g) were the most abundant elements. Conclusion: P. guajava. leaves represent a bioactive matrix with high levels of phenolic compounds and flavonoids, coupled with remarkable antioxidant capacity and a relevant contribution of essential micronutrients. These findings support their potential application in nutraceutical, food, and pharmaceutical industries. Nevertheless, further in vivo studies and clinical trials are needed to validate their efficacy, bioavailability, and safety in complex biological systems.